2009
DOI: 10.1016/j.ejphar.2008.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell cycle events and apoptosis in mediating the anti-cancer activity of a silver(I) complex of 4-hydroxy-3-nitro-coumarin-bis(phenanthroline) in human malignant cancer cells

Abstract: The central objective of the current study was to investigate the potential in vitro anti-proliferative effect of 4-hydroxy-3-nitro-coumarin (hncH), and the mixed-ligand silver (I) complex of 4-oxy-3-nitro-coumarin-bis(phenanthroline), [Ag(hnc)(phen)(2)] using four human-derived model cell lines. In addition, selected mechanistic studies were carried out using the most sensitive of the four cell lines. Results obtained show that the complex could decrease the proliferation of all four cell lines including neop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 64 publications
1
36
0
1
Order By: Relevance
“…Bhattacharyya et al reported that coumarin enhances pro-apoptotic p53, PCNA, Bad, Bax, apoptotic protease activating factor (Apaf), cyt c, caspase-3 and caspase-9 expression in melanoma (skin cancer) cells, and inhibits the anti-apoptotic factors Akt, Bcl-2, Bcl-xL and NF-κB (15). Thati et al also identified that coumarin derivatives enhance the malignancy of pro-apoptotic factors caspase-3 and -9 (16). …”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharyya et al reported that coumarin enhances pro-apoptotic p53, PCNA, Bad, Bax, apoptotic protease activating factor (Apaf), cyt c, caspase-3 and caspase-9 expression in melanoma (skin cancer) cells, and inhibits the anti-apoptotic factors Akt, Bcl-2, Bcl-xL and NF-κB (15). Thati et al also identified that coumarin derivatives enhance the malignancy of pro-apoptotic factors caspase-3 and -9 (16). …”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has focussed on the synthesis and therapeutic applications of a series of silver and copper complexes of coumarin-derived ligands [24][25][26][27][28][29]. More recently we have focused our research efforts on the preparation of a series of coumarinand quinolin-2(1H)-one-triazole-derived Schiff bases and their Cu(II) complexes [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The chemotherapeutic potential of 1,10-phenanthroline and three of its transition metal complexes was determined on two different cancer cells by Deegan et al [48] and they suggested that phen and three metal-phen complexes may have been successful therapeutics. A silver(I) complex of phenanthroline was found to be more potent than cisplatin on HepG2 cells [49]. Gold(III) complexes with bidentate ligands based on the 1,10-phenanthroline and 2,2′-bipyridine scaffolds showed promising anticancer activity against a variety of tumor cell lines [50].…”
Section: Discussionmentioning
confidence: 99%